PENGEMBANGAN HANDOUT BERBASIS KONTEKSTUAL PADA MATERI BARISAN DAN DERET ARITMATIKA SISWA SMAN 1 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Desfina Aisyiah; Hafizah Delyana; Melisa Melisa (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2022)
This research is motivated by the teaching materials in SMAN 1 Six Lingkung which have not been able to make students become active in learning and accustom students to independent learning in solving problems given by the teacher. The aim of this research is to produce contextually based handouts on valid and practical arithmetic sequences and series material. The subjects of this study were students of class XI MIPA SMAN 1 Enam Lingkung, Padang Pariaman Regency. This research is a development research using the Plomp model (2013), which consists of 3 stages, namely preliminary research, prototyping phase, and assessment phase. The limitation of this research is only up to the prototyping phase. The research instrument used was validity test and practicality test. Based on the results of the validator's and mathematics teacher's assessment, the percentage of the final assessment of the validity of teaching materials was 84.33% with a very valid category. Furthermore, the final value of practicality trials with students obtained a percentage of 88.37% in the very practical category. Therefore, it is concluded that the contextual-based Handout on arithmetic sequences and series material is in the category of valid and practical.